Fascicular Phrenic Nerve Neurotization for Restoring Physiological Motion in a Congenital Diaphragmatic Hernia Reconstruction With a Reverse Innervated Latissimus Dorsi Muscle Flap. Issue 2 (August 2015) - Horta, Ricardo; Henriques-Coelho, Tiago; Costa, Joana; Estevão-Costa, José; Monteiro, Diana; Dias, Mariana; Braga, José; Silva, Alvaro; Azevedo, Inês; Amarante, José Manuel
<x xml:space="preserve">Abstract</x> Abstract Congenital diaphragmatic hernia is a severe developmental anomaly characterized by the malformation of the diaphragm. An innervated reversed latissimus dorsi flap reconstruction for recurrent congenital diaphragmatic hernia has been described as an alternative to prosthetic patch repair to achieve pleuroperitoneal separation. However, there is very little supporting scientific data; therefore, there is no real basic understanding of the condition of the phrenic nerve in the absence of diaphragmatic muscle or even the neurotization options for restoring neodiaphragmatic muscle motion. We have reviewed the literature regarding phrenic nerve anatomy and neurotization options, and to our knowledge, this is the first time that the application of a fascicular repair is being described where the continuity of one remaining fascicle of the diaphragm has been preserved close to the phrenic nerve distal division. The procedure was undertaken in a 3 year-old boy, with the diagnosis of congenital large posteromedial diaphragmatic hernia and dependence of mechanical ventilation in consequence of severe bronchopulmonary dysplasia. The phrenic nerve divides itself into several terminal branches, usually three, at the diaphragm level, or just above it. This allows the selective coaptation of separate fascicular branches. In the case described, videofluoroscopy evaluation showed no evidence of paradoxical neodiaphragmatic motion, with synchronous contraction movements and intact pleura-peritoneal separation. The child is now asymptomatic and shows improvement of his previous restrictive pulmonary disease. We believe that fascicular repair can achieve some reinnervation of the flap without jeopardizing the potential of diaphragmatic function by contraction of reminiscent native diaphragm.